Connections Between Amino Acid Metabolisms in Plants: Lysine as an Example - Yang, Qingqing; Zhao, Dongsheng; Liu, Qiaoquan (Frontiers in Plant Science, 2020)
Extensive efforts have been made to fortify essential amino acids and boost nutrition in plants, but unintended effects on growth and physiology are also observed. Understanding how different amino acid metabolisms are connected with other biological pathways is therefore important. In addition to protein synthesis, amino acid metabolism is also tightly linked to energy and carbohydrate metabolism, the carbon-nitrogen budget, hormone and secondary metabolism, stress responses, and so on. Here, we update the currently available information on the connections between amino acid metabolisms, which tend to be overlooked in higher plants. Particular emphasis was placed on the connections between lysine metabolism and other pathways, such as tryptophan metabolism, the tricarboxylic acid cycle, abiotic and biotic stress responses, starch metabolism, and the unfolded protein response. Interestingly, regulation of lysine metabolism was found to differ between plant species, as is the case between dicots and monocots. Determining the metabolic connection between amino acid metabolisms will help improve our understanding of the metabolic flux, supporting studies on crop nutrition.